A Field Test of Eugenol‐Based Anesthesia versus Fish Restraint in Migrating Adult Chinook Salmon and Steelhead. Issue 4 (4th June 2014) - Caudill, Christopher C.; Jepson, Michael A.; Lee, Steven R.; Dick, Travis L.; Naughton, George P.; Keefer, Matthew L.
Abstract: Many studies require the collection and handling of fish, which may have short‐ and long‐term effects on their behavior and survival. We evaluated the effects of AQUI‐S 20E, a eugenol‐based anesthetic, on adult spring Chinook Salmon Oncorhynchus tshawytscha and winter steelhead O. mykiss in the Willamette River, Oregon. We experimentally compared the postrelease behaviors and movement into spawning tributaries of fish radio‐tagged under anesthesia with those of fish radio‐tagged while being manually held in a restraint device. Anesthetized Chinook Salmon were less likely than restrained Chinook Salmon to swim downstream (20% versus 47%), more likely to reascend the fishway at which they were collected (89% versus 60%), and more likely to escape to tributaries (82% versus 47%). The treatment effect persisted after statistically controlling for tag date, release time, and fish size. In contrast to Chinook Salmon, the percentages of anesthetized and restrained steelhead that moved downstream (17%), passed the dam (88–90%), and escaped to tributaries (79–83%) did not differ by handling treatment. Our results highlight that the effects of handling and tagging need to be evaluated, that such effects may be species specific and occur at multiple scales, and that eugenol‐based anesthetic should be used instead of restraining devices for Chinook Salmon. Received July 8, 2013; accepted January 29, 2014